2020
DOI: 10.1177/2333721420923449
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Leisure Activities, Depression and Quality of Life in Community-Dwelling Elderly Koreans

Abstract: Objectives: This study aimed to identify the relationship among leisure activities, depression, and quality of life of community-dwelling elderly in Korea. Methods: We assessed 100 community-dwelling older adults. Leisure participation and leisure exploration were assessed by using the leisure participation for the elderly. Depression was measured using the Korean version of the Short Form of Geriatric Depression Scale, and quality of life was assessed using EQ-5D. Statistical analysis was performed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
2
25
1
3
Order By: Relevance
“…Previous studies (Heo et al, 2013; Kuykendall et al, 2015; Paggi et al, 2016) have demonstrated that older adults who engaged in leisure and recreation activities had superior mental health, as well as longevity (Arem et al, 2015; Paggi et al, 2016; Sirgy et al, 2017). Known mental health benefits to older adults arising from engagement in leisure and recreation activities are improvements in mental health by reducing anxiety, depression, and negative mood state, positively affecting self-esteem, cognitive function, and quality of life (Goodman et al, 2017; Jeong & Park, 2020) . Older adults would likely select leisure and recreation activities for enjoyment, pleasure, and amusement (Lamanes & Deacon, 2019), and those which they find empowering (Kamioka et al, 2013; Lamanes & Deacon, 2019) and adding to their sense of belongingness (Talmage et al, 2020).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Previous studies (Heo et al, 2013; Kuykendall et al, 2015; Paggi et al, 2016) have demonstrated that older adults who engaged in leisure and recreation activities had superior mental health, as well as longevity (Arem et al, 2015; Paggi et al, 2016; Sirgy et al, 2017). Known mental health benefits to older adults arising from engagement in leisure and recreation activities are improvements in mental health by reducing anxiety, depression, and negative mood state, positively affecting self-esteem, cognitive function, and quality of life (Goodman et al, 2017; Jeong & Park, 2020) . Older adults would likely select leisure and recreation activities for enjoyment, pleasure, and amusement (Lamanes & Deacon, 2019), and those which they find empowering (Kamioka et al, 2013; Lamanes & Deacon, 2019) and adding to their sense of belongingness (Talmage et al, 2020).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Furthermore, many of the survey participants reported refraining from engaging in certain activities. There is evidence that sports and leisure activities prevent worsening of psychosocial factors 22,23 . Therefore, the risk of worsening psychosocial factors is likely to increase with the long‐term restriction of activities because of the spread of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Lectura, escritura y uso de internet (17,19,24) Efectos positivos en la depresión y en la calidad de vida.…”
Section: Uso De Tecnología Para Dotación De Servicios Sanitarios Y So...unclassified
“…Actividades sociales y de comunicación (17) Efectos positivos en la depresión y en la calidad de vida Aeróbicos, ejercicios de resistencia (20) Mejora cognitiva.…”
Section: Uso De Tecnología Para Dotación De Servicios Sanitarios Y So...unclassified